Effects of Co2 and Ch4 Emissions on Climate Variability in the Tropics (2012)
Climate variability is indicated as anomalies in weather parameters such as rainfall and temperature. These are being influenced by greenhouse gas emissions such as carbon dioxide (CO2) and methane (CH4), amongst others. This variability is usually studied using General Circulation Models (GCMs) and empirical models obtained from analyses of data at synoptic weather stations. The GCMs give different predictions from model to model due to parameterisations of microprocesses embedded in them. Likewise, empirical models are often applicable to locations of studies and most stations in the tropics are yet to be analysed. Hence, this work was aimed at analysing and modelling both CO2 and CH4 concentrations over the entire tropics with a view to understanding their contributions to climate variability. Daily concentration data of CO2 and CH4 from the 12 stations, with minimum of 10-year data, within latitude 30oN and 30oS were obtained from World Data Centre for Greenhouse Gases, Japan. These data, between January 1996 and December 2005, were analysed using standardized anomalies, moving average and autocorrelation methods. Box-Jenkins iterative method which combines both moving average and auto regression analyses, was employed for modelling the concentrations (i) of the gases as a function of time. The suitability of the developed model was determined by comparing the predicted and measured monthly concentrations of these gases for the period January 2006 to December 2008. The standard deviations (i) of the concentrations of these modelled gases were correlated with Roy Spencer‟s tropical temperature anomaly data to ascertain their warming effect.The standardized anomalies showed seasonal variations and smoothening of these data by moving average revealed monotonic increase with time. The autocorrelation function showed that CO2 can be predicted with higher accuracy than CH4. The developed model was of the form:121111120)120(tctba for CO2 and 222222120)120(tctba for CH4, where ai, bi, c i and t represent the intercept, linear term coefficient, quadratic term coefficient and predictedmonth respectively. The mean annual concentrations calculated using the model for CO2 and CH4 in the northern hemisphere stations ranged from 381.5±0.3 to 384.3±0.3 ppm and 1793.5±1.4 to 1832.9±1.7 ppb respectively, while the measured values ranged from 382.9±0.2 to 384.5±0.2 ppm and 1787.3±1.4 to 1823.3±1.0 ppb respectively.Similar agreement was obtained between calculated and measured values for southern hemisphere stations. The correlation coefficient between predicted and measured concentrations of CO2 and CH4 for year 2006 to 2008 was 0.99 and 0.96 respectively. The i for CO2 and CH4 concentrations in northern hemisphere ranged from 0.3 to 0.9 and 0.5 to 3.3 respectively, while those in southern hemisphere ranged from 0.4 to 0.7 and 0.2 to 4.2 respectively. The i increased with climatic warming and had highest value for 1998, the warmest among the years considered. Concentrations of both CO2 and CH4 increased monotonically with time. The developed model predicted CO2 and CH4 concentrations adequately in the tropics and could also be used to predict their future concentrations and climate warming effectively.